The effect of median nerve mobilization on two point discrimination - Aras Bayram, Gülay; Kaya Ciddi, Pınar; Marangoz, Cafer (Society of Physical Therapy Science, 2022)
[Purpose] Two-point discrimination (TPD) is expressed as the minimum distance at which two mechanical stimuli applied simultaneously to the skin can be perceived as two separate points. The aim of this study was to investigate the effect of median nerve mobilization on TPD in healthy adults. [Participants and Methods] This study included 120 healthy adults. Participants were randomized according to their gender into the Neural Mobilization Group (NMG) and Control Group (CG). Demographic data of the participants (gender, age, height, weight, BMI, smoking) were recorded and TPD measurement was performed with baseline aesthesiometer on the palm with distal phalanges of the thumb, index and middle finger on the right-left hand. After the baseline TPD test, participants in the NMG performed Median Nerve Mobilization for 14 days. Measurements were taken before and after training. [Results] A statistically significant difference was found in all other measurements in both groups, except for the right and left palm TPD measurements in the control group. [Conclusion] It is thought that it would be beneficial to investigate the healing effects of the neural mobilization applications, which include all parts of the nerve line in disease conditions.
Keywords: Two-Point Discrimination; Neural Mobilization; Median Nerve